Business Competition Cases Related to Restrictions on Distribution/Sales of Goods in KPPU Decision Number 15/KPPU-I/2022 - Kurniati, Yeti; Santoso, Edy; Rahmat, Riris Risnayanti; Juliawati, Kania; Rahayu, Mega; Sari, Lucky Nurlita (Formosa Journal of Sustainable Research, 2024)
Market dominance also includes activities that limit the circulation and/or sale of goods and/or services in the relevant market. Related to these activities, these are activities that fall into the category prohibited by law, more precisely activities prohibited by Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. This happened in the case of cooking oil in Indonesia, which in 2021 experienced a shortage. In the decision of the KPPU Panel of Judges, out of 27 Reported Parties, only 7 reported parties were proven legally and convincingly to have committed violations according to Article 19 letter c. The approach used is the rule of reason and an important part to handle the existence of elements of activities to limit the circulation and/or sale of goods and/or services in the relevant market. Restrictions on the circulation/sale of goods in this case cooking oil which causes a shortage are very detrimental to the community. The importance of law enforcement, therefore the KPPU has determined that a law enforcement process will be carried out after evidence of alleged violations of Law Number 5 of 1999 is found